Building students’ voices through critical pedagogy: braiding paths towards the other - Umbarila Gómez, Silvia Patricia (Colombian Applied Linguistics Journal, 2010)
This study attempts to promote social reflection and cultural recognition in the multicultural scenario of the classroom. This is a qualitative study carried out with ninth grade students at a public school in Bogotá. The main objective is enrolling the students in critical pedagogy practices that allow them the construction of the sense of Other. The experience was implemented through the students’ exposure to authentic historical facts in which they acquired knowledge about social, political, and cultural issues. This exposure then encouraged reflection during the classes, empowering the students with a voice to refuse and denounce. Students’ voices were identified and interpreted through the instruments used, video recordings and artifacts. The results highlighted the importance of giving students a voice that enriches their role as citizens in terms of their responsibility and commitment towards Others.